Anatomical and functional outcomes of idiopathic macular hole surgery with fovea-sparing versus conventional internal limiting membrane peeling - Z. A. Rozanova; M. M. Umanets; Filatov Institute of Eye Diseases and Tissue Therapy, NAMS of Ukraine; A. O. Nevska; Ines Buallagui (Ukrainian Society of Ophthalmologists, 2023)
Purpose: To compare fovea-sparing and conventional internal limiting membrane (ILM) peeling in idiopathic macular hole (IMH) surgery in terms of IMH closure type, hole closure incidence and visual outcome. Material and Methods: The ILM was peeled around the IMH in the conventional ILM peeling group. In the fovea-sparing ILM peeling group, an ILM flap was created temporally to the IMH (with an ILM remnant left attached to the margins of the IMH), folded over the hole and stabilized with viscoelastic. Gas tamponade with 20% SF6 or 15% С3F8 was used. In the postoperative period, IMH closure pattern was assessed. Thicknesses of the outer retinal layers, inner retinal layers and retinal nerve fiber layer in the macular region were measured at 1 and 3 months. Results: Totally, 70 patients (15 males and 55 females) had an IMH surgery in 71 eyes. The mean age (SD) was 65.7 (6.8) years. The median IMH duration (interquartile range (IQR)) was 3.0 (1.0-6.0) months, and the mean preoperative BCVA (standard deviation (SD)), 0.19 (0.16). Thirty-four eyes had an IMH surgery with conventional ILM peeling, and 37 eyes, an IMH surgery with fovea-sparing ILM peeling. The two groups were matched in terms of preoperative visual acuity and macular hole duration. IMH closure was achieved in 30/34 eyes (88.2%) in the conventional ILM peeling group and 33/37 eyes (89.2%) in the fovea-sparing ILM peeling group. Particularly, IMH closure was achieved in 13/17 eyes that received gas tamponade with 20% SF6 and 20/20 eyes that received that with 15% С3F8 in the latter group. The rate of correct IMH closure pattern was substantially higher (64% versus 47%) and median postoperative BCVA (IQR), significantly better (0.55 (0.35-0.7) versus 0.43 (0.35-0.6), р = 0.039) in the fovea-sparing ILM peeling group than in the conventional ILM peeling group. An analysis of variance found a significant effect of the type of IMH surgery and IMH closure pattern on the postoperative BCVA (F1 = 5.06, p = 0.027; F2 = 7.9, p = 0.0001). In both groups, we found a significant thinning of the total retinal thickness in the central 1-mm foveal zone at 3 months compared to 1 month after surgery. There was a significant thinning of the outer and inner retinal layers in the conventional ILM peeling group, and no significant thickness changes in the retinal layers in the fovea-sparing group. Conclusion: Our fovea-sparing ILM peeling technique is an effective treatment option for IMHs, and when used with gas tamponade with 15% С3F8, enabled a primary surgery IMH closure rate of 100%.